2010
DOI: 10.1007/s10546-010-9470-7
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic Particle Image Velocimetry Measurements in an Urban-Type Boundary Layer: Insight into Flow Regimes and Incidence Angle Effect

Abstract: An experimental investigation of the three-dimensional flow through an urban-type array (four rows of three cuboid Plexiglas blocks) in a laboratory modelled neutrally stratified atmospheric boundary layer is presented. We concentrate on the effect of the streamwise spacing between adjacent rows defining two different flow regimes (wake interference and skimming flow) as well as the effect of the incident angle of the approaching boundary layer. Stereoscopic particle image velocimetry measurements provide all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It is also crucial to be able to accurately determine 556 R. Vinuesa et al vortex shedding frequencies in complex geometries for adequate structural design in order to avoid large vibrations induced by resonance. For instance, the flow around one building under the influence of various surface layer conditions was studied experimentally by Corke et al, [3] and pollutant dispersion in a number of urban environments was characterised by Nagib and Corke [4] and Monnier et al [5] by means of wind tunnel testing. The relation between surface mounted cylinders and jets emanating from the surface has been studied and characterised by Fric and Roshko.…”
Section: Introductionmentioning
confidence: 99%
“…It is also crucial to be able to accurately determine 556 R. Vinuesa et al vortex shedding frequencies in complex geometries for adequate structural design in order to avoid large vibrations induced by resonance. For instance, the flow around one building under the influence of various surface layer conditions was studied experimentally by Corke et al, [3] and pollutant dispersion in a number of urban environments was characterised by Nagib and Corke [4] and Monnier et al [5] by means of wind tunnel testing. The relation between surface mounted cylinders and jets emanating from the surface has been studied and characterised by Fric and Roshko.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the study presented by Monnier et al [71] shows how the PIV strategy can produce relevant results that deepen the understanding of the fundamental drivers of urban flows.…”
Section: Closed-environment Experimentsmentioning
confidence: 80%
“…In Figure 7 we show the schematic representation proposed by Hunt et al [121], where a total of 4 vortical structures are identified: the horseshoe vortex (A) which forms around the obstacle; the roof vortex (B) and the vortices on the obstacle sides (C), which have a close interaction with the wake; and finally the well-known arch vortex (D) on the leeward side of the obstacle, which will be discussed in detail below. Note that there are a number of methods used to identify coherent structures, and although they do not exhibit significant differences when applied to turbulent flows [122], they may emphasize slightly different phenomena when applied to urban environments [71]. Furthermore, we argue that the use of adequate thresholds may help to discern intense event inherent to turbulent fluctuations and large-scale effects induced by the geometry.…”
Section: Flow Structuresmentioning
confidence: 88%
See 2 more Smart Citations